Application of Analytical Hierarchical Process (AHP) in Development of Suitability Model for Rice Production in Taraba State - A, Ezra; A.A, Adebayo; A. S, Umar (International Journal of Sustainable Agricultural Research, 2020)
This research was aim at applying Multi-Criteria Decision Making (MCDM) in Agro-Climatic Zoning of Taraba State for rice Production. Climatic variables, Rice Yield, Digital Elevation Model (DEM), Land Sat 8 (OLI) and Soil Texture map were the data used. Climatic data of the state were analyzed over time and Space using trend and spatial analysis tools in excel and Arc GIS respectively, while correlation and stepwise regression analysis between rice yield and the climatic variables were analyzed in SPSS. Mean temperature, August and September rainfalls were identified to be the critical Climatic factors affecting the growth and yield of rice in the State. The highly suitable cover places such as; Lisasam, Takum, Donga, Wukari, Mutum Biyu and Bali while the suitable area occupy places like Serti, Lau, Sunkani, Jalingo and Lankaviri. Suitability map produced with NDVI showed that the highly suitable area for Rice cultivation reduced from 31.93% to 28.76%. In regards to this findings, cultivation of rice should be encourage in Highly Suitable and Suitable zones of the State while cultivation of alternative crops other than rice in not suitable area is very important in reducing the risk of crop failure. In addition, application of Multi Criteria Decision Making (MCDM) a Remote Sensing and GIS tool and NDVI plays a significant role in Agro-climatic suitability zoning, as such, the tools are recommended in Agro-climatic research.